Clinical Nurse Levels and Access to EBP Resources: Analyzing Evidence-Based Practice among Indonesian Perioperative Nurse - Ikar Swito; Alfrina Yuniarti; Indah Nur Insani (GLOBAL HEALTH SCIENCE GROUP, 2025)
The clinical nurse career pathway nurses has been in place since 2017. Objective: this study aims to analyze the influence of nurse position level on the implementation of evidence-based practices in operating rooms in Indonesia. survey method used an online questionnaire involving 1075 respondents of operating room nurses actively working in hospitals. implementation of EBP in the operating room requires the role of nurse mentors with better qualifications in research and evidence-based practice. Nurses' education level is important in practice and nurses working in higher class hospitals, such as class A hospitals, also showed more positive attitudes towards evidence-based practice. The role of the nurse manager is important as there was found to be no significant difference between the nurse manager and the head of the room in the implementation of evidence-based practice. implementation of career paths for nurses, especially in operating rooms, is going in the right direction, the beliefs and practices of nurses at various levels have been reflected in the competencies expected from the Ministry of Health regulations.